1997
DOI: 10.1210/jcem.82.6.4026
|View full text |Cite
|
Sign up to set email alerts
|

Antiresorptive Therapy in Hyperthyroid Patients: Longitudinal Changes in Bone and Mineral Metabolism

Abstract: The effect of antiresorptive therapy with nasal calcitonin (CT) in recently diagnosed hyperthyroid patients on conventional medical therapy as well as the evolution of bone metabolism were assessed. Forty-five patients with recent-onset hyperthyroidism (Ͻ12 weeks) were sex and menopause stratified and randomly allocated to treatment with carbimazole (Neotomizol), carbimazole plus low dose CT (Calsynar; 100 IU/day, 2 days/week), or carbimazole plus high dose CT (Calsynar; 100 IU/day, 14 days/month). Bone minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
3
16
0
4
Order By: Relevance
“…The values were expressed as grams per square centimeter and as the z score (number of standard deviations adjusted by age and sex) in comparison with a healthy Spanish reference population (1,221 males, 1,331 females). [20][21] As previously described, 22 our laboratory in vivo (with persons) precision has a long-term coefficient of variation lower than 2% at lumbar and femoral sites of measurement. Stability of the instrument with time was checked by a daily scan of a spine phantom of known composition (Hologic).…”
Section: Methodsmentioning
confidence: 57%
“…The values were expressed as grams per square centimeter and as the z score (number of standard deviations adjusted by age and sex) in comparison with a healthy Spanish reference population (1,221 males, 1,331 females). [20][21] As previously described, 22 our laboratory in vivo (with persons) precision has a long-term coefficient of variation lower than 2% at lumbar and femoral sites of measurement. Stability of the instrument with time was checked by a daily scan of a spine phantom of known composition (Hologic).…”
Section: Methodsmentioning
confidence: 57%
“…In a study that supports the effect of estradiol observed here, Franklyn et al (1995) reported that estrogen replacement therapy abolished the reduction in femoral and vertebral BMD in postmenopausal women with previous thyrotoxicosis and subsequent T4 therapy. In studies by Kung and Yeung (1996) and Jodar et al (1997), intranasal calcitonin provided no additional benefit over calcium or attainment of a euthyroid state, respectively. However, alendronate, a bisphosphonate, increased BMD Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Estes resultados diferem dos resultados descritos em humanos, em que ocorre aumento tanto dos marcadores da formação como da reabsorção óssea (GARNERO et al, 1994;JÓDAR et al, 1997) e diminuição da massa óssea (RAISZ, 1999). Aparentemente o período experimental não foi suficiente para fazer com que os efeitos da reabsorção fossem superiores ao da formação, mesmo tendo havido diminuição da DMO, sugerindo que, nos estágios precoces, não há predomínio da atividade osteoclástica.…”
Section: Resultsunclassified
“…Só existe uma descrição da diminuição da DMO em gatos com hipertireoidismo (COSTA et al, 2006), sendo que achados semelhantes foram obtidos neste estudo. A redução significativa da DMO também foi descrita em humanos com hipertireoidismo (JÓDAR et al, 1997;KUMEDA et al, 2000), indicando perda da massa óssea (RAISZ, 1999). Este fato também foi descrito em ratos submetidos a um curto período de tireotoxicose (KUNG & NG, 1994).…”
Section: Resultsunclassified
See 1 more Smart Citation